Increasing Students' Hardiness and Self-Efficacy through Islam-based SFBC Group Counseling - Labibah, Azmia Khafidzotul; Anwar Sutoyo; Ali Murtadho (Jurnal Bimbingan Konseling, 2024)
Various activities at boarding school require students to own high hardiness and self-efficacy. Regarding this issue, the present study strived for analyzing the effectiveness of the Islamic-based Solution Focused Brief Counseling (SFBC) group counseling to increase the hardiness and self-efficacy of students at MTs Negeri 2 Brebes. An experimental method with the design of pretest-posttest control group was employed by involving 16 students. Based on the Wilcoxon test, the Islamic-based SFBC group counseling could increase the hardiness and self-efficacy of students at MTs Negeri 2 Brebes. Thus, the future studies can use SFBC counseling to increase matters related to human perspectives, such as self-confidence.